Simulation on the Management of Lithium-ion Batteries' thermal Runaway via Liquid Cooling and Phase Change Barrier. Issue 1 (1st December 2022) - Xu, Haihua; Wu, Senming; Chen, Ying; Luan, Weiling
Abstract: In recent years, vehicle power battery safety accidents have occurred frequently, threatening personal safety, commercial promotion, and social benefits. The escalation of accidents is mainly caused by thermal runaway propagation (TRP) of lithium-ion batteries (LIBs). Therefore, exploring effective TRP control methods is becoming a hotspot for ensuring the safety and performance of electric vehicles. This is pap established, a three-cell TRP mode for the commercial LIB through COMSOL Multiphysics software, which was then verified by experimental results. Then an eight-cell TRP model is constructed to study the effects of thermal insulation and heat dissipation on the TRP characteristics. The results indicate that the phase-change thermal insulation layer shows a strong thermal resistance on the TRP compared with the ordinary thermal insulation layer when the insulation layer is applied between the cells. With the increase of the thickness of the phase change thermal insulation layer, the TRP time became longer while the TRP was not suppressed. A liquid cooling combined with the phase change insulation layer between the cells is conducted to obtain the thermal resistance of TRP, which shows a significant guide for the thermal safety design of LIBs.